Penerapan Cooperative Integrated Reading And Composition (CIRC) Untuk Meningkatkan Kemampuan Mahasiswa Semester V Fakultas Hukum UMSU terhadap Mata Kuliah Kemahiran Hukum I - Nurhilmiyah Dosen Fakultas Hukum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Abstrak Latest situation of student in the class shows ineffectively achievement of students, learning process in the class that make a boreness, probability it happened because of applicate of wrong method in the class. Lecture was just applicate speech method with one way traffic communication.This research used the qualitative approach with descriptive analysis. Data are consist of secondary data and primary data directly from classes sources. Population of the research is fifth semester students Faculty of Law UMSU which taught by researcher her self. Sample are Class C-2 and Class B-2 of 2013/2014 academic year. The respondens are whole of student’s of the two classes which they are totally 79 (seventy nine) students at all. The aim of this writing is to see student’s activeness in learning process on the law skill’s subject in the class during fifth semester. Indeed, to getting up result of reachment study successfully with Cooperative Integrated Reading And Composition (CIRC). Base on research result, the application of learning model of Cooperative Integrated Reading And Composition (CIRC) is purpose to enrich students’s ability in learning process for Law Skill’s subject or Scientific Result Writing. Its learning model application on that subject make higher up student’s achievement and have the skill to write law cases scientific. Key words: reachment of ability, The Law Skill Subject, Scientific Result Writing, Cooperative Integrated Reading And Composition (CIRC)